The impact of grazing on forage quality of the herbaceous vegetation in the Mamora cork oak forest, Morocco - Alami, M. Mejjati; Bedell, T. E.; Sharrow, S. H.; Berkat, O. (African Journal of Range & Forage Science, 1997)
This research was conducted in the Mamora cork oak forest of Morocco to describe the impacts of sheep grazing (no use, 35% use, 70% use) in March, April, May and June of 1987 and 1988 on seasonal changes in forage quality of the herbaceous vegetation. The study showed that trends in herbage quality were related mainly to plant maturity. As more species mature, forage quality declines and falls below animal nutritional requirements, especially for young animals. With declining forage quality, the manager has the option of moving stock to areas of less-mature forage, supplementing the forage or modifying the demand placed upon it.
doi: 10.1080/10220119.1997.9647913doi: 10.1080/10220119.1997.9647913The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: crude protein; IVOMD; Mediterranean-type climate; minerals; time of grazing

The impact of grazing on forage quality of the herbaceous vegetation in the Mamora cork oak forest, Morocco - Alami, M Mejjati; Bedell, T E; Sharrow, S H; Berkat, O (African Journal of Range & Forage Science, 1997)
This research was conducted in the Mamora cork oak forest of Morocco to describe the impacts of sheep grazing (no use, 35% use, 70% use) in March, April, May and June of 1987 and 1988 on seasonal changes in forage quality of the herbaceous vegetation. The study showed that trends in herbage quality were related mainly to plant maturity. As more species mature, forage quality declines and falls below animal nutritional requirements, especially for young animals. With declining forage quality, the manager has the option of moving stock to areas of less-mature forage, supplementing the forage or modifying the demand placed upon it.
doi: 10.1080/10220119.1997.9647913
Keywords: crude protein; IVOMD; Mediterranean-type climate; minerals; time of grazing